La expresión artística como estrategia metodológica para el desarrollo del pensamiento lógico-matemático en las niñas y niños de 3 a 4 años de la Escuela de Educación Básica 18 de Noviembre, periodo académico 2021-2022. - Acaro Veintimilla, Angie Salomé (2022)
This research work titled: THE ARTISTIC EXPRESSION AS A METHODOLOGICAL STRATEGY TO LOGICAL-MATHEMATICAL THINKING DEVELOPMENT IN CHILDREN FROM 3 TO 4 YEARS OLD FROM THE BASIC EDUCATION SCHOOL 18 DE NOVIEMBRE, ACADEMIC PERIOD 2021-2022., aimed to promote the development of logical-mathematical intelligence using artistic expressions as a methodological strategy on children from the initial grade II. The present work was developed with a mixed focus, correlational scope, and a quasi-experimental design. Two methods were used: 1) Analytic-Synthetic, and 2) Inductive-deductive. An interview was conducted with the classroom teacher, and a TEMT tool was applied to a sample population of 12 4-years-old. Results from the pre-Test were significantly different from those of the post-Test. Initially, 67% of preschoolers reached a “very low” level. However, once the alternative proposal, “Little artists, great thinkers,” was applied, satisfactory changes were obtained, i.e., 83% of the population reached a “very good” level regarding logical-mathematical thinking. In addition, they could use early mathematical concepts, e.g., comparison, classification, correspondence, seriation, counting and numbers. Besides, identify basic notions like time, space, shape, and color. Therefore, concluding that the “Artistic Expression” is an effective methodological strategy to work logical-mathematical intelligence at an early age. However, it is necessary that the educator design diary activities that include this practical approach to daily activities to ensure real learning. Keywords: strategy, artistic expression, thinking/intelligence, logic-mathematics, initial grade II.